PENGARUH METODE INKUIRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI POKOK EKSPONEN DI KELAS X SMA N 1 BATANG TORU - Fitriani Fitriani (MES: Journal of Mathematics Education and Science, 2016)
Abstract The background of this research problem is that there are student who are not able to use the properties of exponents and are not able to solve the problems exponent while teaching method used is a meaningful method is the method of inquiry (discovery). The main issues discussed in this study is there any influence on the results of the use of inquiry method of learning mathematics students in the subject matter exponent in class X SMA Negeri 1 Batang Toru. This study aims to explain extent of the influence of the methods of inquiry the math learning outcomes of students in the subject matter exponent in class X SMA Negeri 1 Batang Toru. Calculation of the two variables obtained by the average value of the variable X (inquiry method) is 43.77 are "enough" while the variable Y (the results of students' mathematics learning in the subject matter exponent) ie 14.81 are "enough". Based on the calculations in mind that r calculated at 0.7932 then thitung 8.4406 and 2.0189 ttable turns thitung ttabel, then the hypothesis is accepted / approved, so it can be concluded that a significant difference between the use of methods of inquiry to the results of students' mathematics learning in the subject matter exponent in class X SMA Negeri 1 Batang Toru with the category of "strong". KeywordsEffects, Methods of Inquiry, Mathematics Learning Outcomes.